2007
DOI: 10.1111/j.1467-8721.2007.00480.x
|View full text |Cite
|
Sign up to set email alerts
|

Event Segmentation

Abstract: One way to understand something is to break it up into parts. New research indicates that segmenting ongoing activity into meaningful events is a core component of ongoing perception, with consequences for memory and learning. Behavioral and neuroimaging data suggest that event segmentation is automatic and that people spontaneously segment activity into hierarchically organized parts and sub-parts. This segmentation depends on the bottom-up processing of sensory features such as movement, and on the top-down … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
268
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(284 citation statements)
references
References 15 publications
12
268
1
3
Order By: Relevance
“…Although Wayang generates explanations after each input, there is some evidence that people sometimes construct explanations only when their predictions fail (Leake, 1995;Zacks & Swallow, 2007). We plan to do a deeper literature review on this question, and perhaps to alter Wayang accordingly.…”
Section: Resultsmentioning
confidence: 99%
“…Although Wayang generates explanations after each input, there is some evidence that people sometimes construct explanations only when their predictions fail (Leake, 1995;Zacks & Swallow, 2007). We plan to do a deeper literature review on this question, and perhaps to alter Wayang accordingly.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the visualization strategy is based on findings on the role of (1) segmentation of complex events [15], and (2) a first-person perspective [16] for human perception and action learning. However, it must be added that a third-person perspective (e.g., a student watching the teacher performing) has its own benefits with respect to action learning [16].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the visualization of basic step models, we take into account two aspects involving the perception and understanding of complex multimodal events, like dance figures. First, research has shown that segmentation of ongoing activity into smaller units is an automatic component of human perception and functional for memory and learning processes [1,15]. For this, we applied algorithms that segment the continuous stream of motion information into a concatenation of elementary gestures (i.e., dance steps) matching the beat pattern in the music (cf., [6]).…”
Section: User-and Body-centered Approachmentioning
confidence: 99%
“…Studies have consistently shown that people's experiences of the world consist of segmenting the ongoing flow of perceptual information into discrete events instead of passively responding to stimuli (Zacks & Swallow, 2007). Event boundaries are of utmost importance in event perception, because they are the breakpoints where significant changes in both perceptual and conceptual representations take place.…”
Section: Introductionmentioning
confidence: 99%